Status of Start-ups in Hills and Planes of Uttarakhand: A Comparative Study - Narendra Kumar; Dr. L. K. Singh (International Journal of Engineering and Management Research, 2021)
The start-up ecosystem plays a critical role in the growth & development of a society. The reason behind creation of Uttarakhand as a separate state is to have a balanced growth of people in Hills. The start-up policy is a phenomenon that ensures balanced growth by offering equal opportunities to all the segments of the society. Start-up encourages people to initiate and contribute in the economic activity at their home town and to be vocal for local. In this paper start-up ecosystem in Uttarakhand is analysed. The objective of the study is to status and comparisons of start-ups between Hills and Plane region of Uttarakhand. This study will help to design the policy to healthy growth of start-ups in rural and hilly zones of the state. Start-ups that qualify the parameters of start-up policy of Uttarakhand are taken for the study.